IMPLEMENTASI METODE BELAJAR SAMBIL BERMAIN UNTUK MENINGKATKAN LITERASI DAN NUMERASI SISWA SDN LEMBAH HARAPAN - Ribka Yago; Miska Sarah; Rusmini Rusmini; Kusmadi Kusmadi; Nasriani Nasriani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Madako Tolitoli, 2025)
Elementary education is a fundamental foundation for developing children’s quality, particularly in literacy and numeracy, which are key to future academic success. At SDN Lembah Harapan, students still face challenges in achieving basic competency standards in both skills. This program targeted all students, focusing on classes dominated by those with low literacy and numeracy abilities. Initial observations were conducted in July to identify issues, followed by program implementation in August through a Community Service (KKN) activity. The program employed a Participatory Action Research (PAR) approach, emphasizing active involvement of students, teachers, and university students. A learning-through-play method was applied as an innovative strategy to create an engaging, interactive environment that enhances motivation and participation. The program was designed based on constructivist and active learning theories, highlighting direct student involvement. Educational games were used to strengthen literacy and numeracy skills while developing social-emotional competencies. The results indicated increased learning interest, classroom participation, and understanding of basic literacy and numeracy concepts. These findings confirm that learning-through-play with a PAR approach can serve as an effective alternative to support the development of elementary students’ foundational competencies.